2015
DOI: 10.1007/s40737-015-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Clubhouse Community Support for Life: Staff–Member Relationships and Recovery

Abstract: With signs that early interventions for severe mental illness have at best only a modest impact on longerterm outcome, a need for a long-term care and support system that facilitates recovery is resurfacing. This article describes a well-established long-term support program, the clubhouse model, drawing on qualitative interview data from 105 users and 25 staff from five clubhouses in the U.S. and Finland, which was analyzed using a grounded theory approach. Recurrent patterns of transformative life changes em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Finally, the results of this study correspond with those of previous international research in the field (Biegel et al, 2013;Jung & Kim, 2012;Norman, 2006;Pardi & Willis, 2018;Roth, 2017;Tanaka et al, 2015;Tanaka & Davidson, 2015a, 2015b, suggesting that being a Clubhouse member is a similar experience across countries, social systems, and cultures.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Finally, the results of this study correspond with those of previous international research in the field (Biegel et al, 2013;Jung & Kim, 2012;Norman, 2006;Pardi & Willis, 2018;Roth, 2017;Tanaka et al, 2015;Tanaka & Davidson, 2015a, 2015b, suggesting that being a Clubhouse member is a similar experience across countries, social systems, and cultures.…”
Section: Discussionsupporting
confidence: 88%
“…However, our results also show that staff members play a decisive role in whether members feel comfortable in the community. Similarly, previous studies indicated that poor relationships with staff, especially related to disruption of egalitarian status within the Clubhouse, is a major reason for members having a negative perception of the community (Roth, 2017;Tanaka et al, 2015), thus their existential stability.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…family, friends, staff) was more influential in these respects. Access to enabling social environments such as those available in DC and clubhouses can, through the long-term support they offer, provide a safety net from which the users can benefit in their recovery process (Tanaka, Craig, & Davidson, 2015). Several researchers argue, however, that there is a risk in relying on relationships tied to programmes and that the programmes should facilitate support systems in the community (Bonavigo, Sandhu, Pascolo-Fabrici, & Priebe, 2016).…”
Section: Introductionmentioning
confidence: 99%